Rubber seed clones identification using LDR module combined with Arduino - Adzmi, Muhammad Azuan Shah (2013)
This paper studies the rubber seed clones identification are presented using LDR sensors and Arduino as a controller. The main objective of this project is to create an intelligent and simple identification of rubber seed that can recognize the clones based on colour being reflected by the LDR module sensor. Rubber seed clones have different textures and colour characteristic though observation. The functions of this project are to select the best rubber tree series by using a light dependent resistor (LDR) for analyse the intensity of light being reflected through a surface rubber seed. These projects need to identify five types of rubber seed clones. There are RRIM 2009, RRIM 2016, RRIM 2008, RRIM 2011 and RRIM 2005. The three of LDR module sensors are used and located at different distance to take the sample of reading. The device measure the percentages of reflectance based on the intensity of light reflected from the rubber seed surface. The output voltage measurement is then analysed using recommended statistical test to identify the type of rubber seed. The Microsoft Office Excel was used to analysis the average voltage that converts from light reflect by taking 30 sample readings from 5 different clones. The analyses are shown in TABLE and graph and decided to take the average range as a conclusion to compare the type of every clone.